Summary for Policy-makers: Arctic Pollution Issues 2015. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2015)
AMAP, 2015. Summary for Policy-makers: Arctic Pollution Issues 2015. This document presents the policy-relevant findings of the AMAP 2015 assessments of POPs (trends), human health, and radioactivity in the Arctic.